Partnerships in maths parents and schools : the IMPACT Project - Merttens, Ruth.; Vass, Jeff. (Falmer Press, 1993)
The IMPACT Project involves individuals concerned with formal maths education and aims to bring parents and children together to share in maths activities. Each part of this book focuses on a particular aspect of parental involvement.